1997
DOI: 10.1074/jbc.272.33.20907
|View full text |Cite
|
Sign up to set email alerts
|

Induction of IgE Antibody Responses by GlutathioneS-Transferase from the German Cockroach (Blattella germanica)

Abstract: We report that a major 23-kDa allergen from German cockroach (Blattella germanica) is a glutathione S-transferase (EC 2.5.1.18; GST). Natural B. germanica GST, purified from cockroach body extracts by glutathione affinity chromatography, and recombinant protein expressed in Escherichia coli using the pET21a vector, showed excellent IgE antibody binding activity. B. germanica GST caused positive immediate skin tests in cockroach-allergic patients using as little as 3 pg of recombinant protein. The NH 2 -termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
115
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 54 publications
5
115
2
Order By: Relevance
“…The present study showed that when there was cockroach home infestation (more than 5 dead insects after pesticide), there was also a 3.45 higher frequency of asthma in the children than when there was no cockroach infestation, in agreement with data of studies which used different techniques for the assessment of exposure (5,13).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The present study showed that when there was cockroach home infestation (more than 5 dead insects after pesticide), there was also a 3.45 higher frequency of asthma in the children than when there was no cockroach infestation, in agreement with data of studies which used different techniques for the assessment of exposure (5,13).…”
Section: Discussionsupporting
confidence: 80%
“…Although the combination of cockroach allergy and exposure to high levels of infestation can explain some aspects of asthma among these patients, a clear causal relationship between these factors has not been sufficiently demonstrated (13,14) and more information should be obtained about this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of allergens have been identified that stimulate IgE production and cause IgEmediated disease (6)(7)(8)(9). Although considerable information exists on the identification, purification, and cloning of inhaled allergens (pollens, dust mites, animal danders, insects, and fungi), few food allergens have been identified and studied.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the activity of these enzymes is associated with resistance to all of the major classes of insecticides (Fournier et al, 1992;Prapanthadara et al, 1993;Huang et al, 1998;Ranson et al, 2001;Vontas et al, 2001;Ortelli et al, 2003;Enayati et al, 2005;Lumjuan et al, 2005). Due to the important role of GST, GST genes have been cloned from several insect species (Snyder et al, 1995;Arruda et al, 1997;Ranson et al, 1997;Ding et al, 2003;Valles et al, 2003;Claudianos et al, 2006;Yamamoto et al, 2005Yamamoto et al, , 2006Yamamoto et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%